Coronary fat content evaluated by morphometry in patients with severe atherosclerosis has no relation with serum lipid levels - Braz Jr.,D.J. (2007)
The relationship between lipid serum levels and coronary atherosclerotic plaque fat content was studied in 51 necropsy patients. Serum lipids were measured by standard techniques, during life, in the absence of lipid-lowering drugs. Intima, intimal fat and media areas were measured using a computerized system in cryosections of the odd segments of the right, anterior descending and circumflex coronary arteries stained with Sudan-IV. Mean intimal and lipid areas were 5.74 ± 1.98 and 1.22 ± 0.55 mm² (22.12 ± 8.48%) in 26 cases with high cholesterol (³200 mg/dL) and 4.98 ± 1.94 and 1.16 ± 0.66 mm² (22.75 ± 9.06%) in 25 cases with normal cholesterol (<200 mg/dL; P > 0.05). Patients with high levels of low-density lipoprotein (³130 mg/dL, N = 15) had a higher intima/media area ratio than those with normal levels of low-density lipoprotein (<130 mg/dL, N = 13, P < 0.01). No significant difference in the morphometrical variables was found in groups with high or low serum levels of triglycerides (³200 mg/dL, N = 13 vs <200 mg/dL, N = 36) or high-density lipoprotein (³35 mg/dL, N = 11 vs <35 mg/dL, N = 17). The association between the morphological measurements and serum levels of cholesterol, its fractions, and triglycerides was also tested and the correlation coefficients were low. Although high cholesterol is a risk factor, we show here that in patients with severe atherosclerosis blood cholesterol and triglyceride levels seem to have little influence on coronary lipid content, indicating that other factors may contribute to arterial lipid deposition and plaque formation.